WEB 2.0 tools in English Project Based Learning at Elementary and High Schools in Kabupaten Pinrang - Kiki Rezki Ananda; Magdahalena Tjalla; Zulfah Fakhruddin; Mujahidah Mujahidah; Abdul Haris Sunubi (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This research investigates the Web 2.0 tools utilized by teachers and students in English project-based learning (PBL) across elementary and high schools in Kabupaten Pinrang. The study aims to identify the types of digital tools utilized by teachers and students. A descriptive survey design was employed, involving 31 English teachers and 70 students from junior and senior high schools. Data were collected through online questionnaires and analyzed using descriptive statistics. The findings reveal that Canva (93.5%), YouTube (87.1%), and WhatsApp (77.4%) are the most commonly used tools by teachers, while students favor YouTube (60%), WhatsApp (51.4%), and Google Classroom (41.4%). Teachers primarily utilize Web 2.0 tools for content creation, communication, and assessment, while students use them for content exploration and project execution. Challenges identified include the limited adoption of collaborative platforms and synchronous communication tools due to digital literacy gaps and connectivity issues.